(untitled) (JED (Jurnal Etika Demokrasi), 2022)
This study aims to describe the literacy learning method in improving students’ reading skills at SDN 3 Ngringin, Nganjuk. This research method used is descriptive qualitative. The study obtained primary data through in-depth interviews and observations of informants, which consisted of several elements, namely, school principals, teachers, and students. The informants were chosen because they were directly involved in the literacy teaching-learning method at SDN 3 Ngringin. The school was chosen because it is a formal educational institution which is categorized as underdeveloped. This study uses an analysis of learning theory from Pinnell and Fountas. The results showed that the literacy learning method applied by the student of Kampus Mengajar program got positive responses from students. This can be seen from the enthusiasm and motivation of students in understanding the learning materials. The learning outcomes can improve students’ reading literacy skills. Penelitian ini bertujuan untuk mendeskripsikan metode pembelajaran literasi di SDN 3 Ngringin, Nganjuk dalam meningkatkan keterampilan membaca siswa. Metode penelitian ini adalah kualitatif yang bersifat deskriptif. Penelitian memperoleh data primer melalui wawancara wawancara mendalam dan observasi terhadap informan, yang terdiri dari beberapa unsur yaitu, kepala sekolah, guru, dan siswa. Para informan tersebut dipilih, karena mereka yang terlibat lansung dalam metode pembelajaran literasi di Sekolah Dasar Negeri 3 Ngringin. Sekolah ini dipilih sebagai tempat penelitian karena merupakan lembaga pendidikan formal yang dikategorikan tertinggal. Penelitian ini menggunakan analisi teori pembelajaran dari Pinnell and Fountas. Hasil penelitian menunjukkan bahwa metode pembelajaran literasi yang diterapkan pada mahasiswa Kampus Mengajar mendapatkan tanggapan postif dari siswa. Hal ini dapat dilihat dari antusiasme dan motivasi siswa dalam memahami materi pembelajaran. Hasil pembelajaran tersebut dapat meningkatkan keterampilan literasi membaca siswa.